In vivo shell-like fractures of veneered-ZrO2 fixed dental prostheses - Belli, Renan; Scherrer, Susanne S.; Reich, Sven; Petschelt, Anselm; Lohbauer, Ulrich (Case Studies in Engineering Failure Analysis, 2014)
Fractographic analyses are performed in two fixed dental prosthetic reconstructions made of ZrO2 frameworks covered by a veneering ceramic that fractured during function in the mouth. Processing histories, material properties, recovered broken parts and replicas of the fracture surface were used, along with fractographic markings to determine fracture origins and cause of failure. A shell-like fracture pattern was found common for both cases, although different factors were identified to be involved in each fracture event. Internal thermal residual stresses and occlusal surface defects from localized contact overloading were found to precipitate the fracture in Case 1, whereas extreme occlusal surface damage from sliding chewing contact was determinant in the fracture of Case 2. The interface between the veneering ceramic and the ZrO2 framework was unaffected by the fractures.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Contact damage; Dental ceramics; Dental fractography; Dental prosthesis; Glass-ceramic; Zirconia